Preparation and characterization of AFM tips with nitrogen-vacancy and nitrogen-vacancy-nitrogen color centers - Orzechowska, Zuzanna; Mrózek, Mariusz; Gawlik, Wojciech; Wojciechowski, Adam (Photonics Letters of Poland, 2021)
We demonstrate a simple dip-coating method of covering standard AFM tips with nanodiamonds containing color centers. Such coating enables convenient visualization of AFM tips above transparent samples as well as using the tip for performing spatially resolved magnetometry. Full Text: PDF References G. Binnig, C. F. Quate, C. Gerber, "Atomic Force Microscope", Phys. Rev. Lett. 56, 930 (1986). CrossRef F .J. Giessibl, "Advances in atomic force microscopy", Rev. Mod. Phys. 75, 949 (2003). CrossRef S. Kasas, G. Dietler, "Probing nanomechanical properties from biomolecules to living cells", Eur. J. Appl. Physiol. 456, 13 (2008). CrossRef C. Roduit et al., "Stiffness Tomography by Atomic Force Microscopy", Biophys. J. 97, 674 (2009). CrossRef L. A. Kolodny et al., "Spatially Correlated Fluorescence/AFM of Individual Nanosized Particles and Biomolecules", Anal. Chem. 73, 1959 (2001). CrossRef L. Rondin et al., "Magnetometry with nitrogen-vacancy defects in diamond", Rep. Prog. Phys. 77, 056503 (2014). CrossRef C. L. Degen, "Scanning magnetic field microscope with a diamond single-spin sensor", Appl. Phys. Lett. 92, 243111 (2008). CrossRef J. M. Taylor et al., "High-sensitivity diamond magnetometer with nanoscale resolution", Nat. Phys. 4, 810 (2008). CrossRef J. R. Maze et al., "Nanoscale magnetic sensing with an individual electronic spin in diamond", Nature 455, 644 (2008). CrossRef L. Rondin et al., "Nanoscale magnetic field mapping with a single spin scanning probe magnetometer", Appl. Phys. Lett. 100, 153118 (2012). CrossRef J. P. Tetienne et al., "Nanoscale imaging and control of domain-wall hopping with a nitrogen-vacancy center microscope", Science 344, 1366 (2014). CrossRef R. Nelz et al., "Color center fluorescence and spin manipulation in single crystal, pyramidal diamond tips", Appl. Phys. Lett. 109, 193105 (2016). CrossRef G. Balasubramanian et al., "Nanoscale imaging magnetometry with diamond spins under ambient conditions", Nature 455, 648 (2008). CrossRef P. Maletinsky et al., "A robust scanning diamond sensor for nanoscale imaging with single nitrogen-vacancy centres", Nat. nanotechnol. 7, 320 (2012). CrossRef L. Thiel et al., "Quantitative nanoscale vortex imaging using a cryogenic quantum magnetometer", Nat. nanotechnol. 11, 677 (2016). CrossRef F. Jelezko et al., "Single spin states in a defect center resolved by optical spectroscopy", Appl. Phys. Lett. 81, 2160 (2002). CrossRef M. W. Doherty et al., "The nitrogen-vacancy colour centre in diamond", Phys. Rep. 528, 1 (2013). CrossRef C. Kurtsiefer, S. Mayer, P. Zarda, H. Weinfurter, "Stable Solid-State Source of Single Photons", Phys. Rev. Lett. 85, 290 (2000). CrossRef A. Gruber, A. Dräbenstedt, C. Tietz, L. Fleury, J. Wrachtrup, C. Von Borczyskowski, "Scanning Confocal Optical Microscopy and Magnetic Resonance on Single Defect Centers", Science 276, 2012 (1997). CrossRef F. Dolde et al., "Electric-field sensing using single diamond spins", Nat. Phys. 7, 459 (2011). CrossRef K. Sasaki et al., "Broadband, large-area microwave antenna for optically detected magnetic resonance of nitrogen-vacancy centers in diamond", Rev. Sci. Instrum. 87, 053904 (2016). CrossRef A. M. Wojciechowski et al., "Optical Magnetometry Based on Nanodiamonds with Nitrogen-Vacancy Color Centers", Materials 12, 2951 (2019). CrossRef I. V. Fedotov et al., "Fiber-optic magnetometry with randomly oriented spins", Opt. Lett. 39, 6755 (2014). CrossRef